IMPLEMENTASI PEMBELAJARAN BERBASIS ETHNO-EDUTAINMENT UNTUK MENINGKATKAN KARAKTER CINTA TANAH AIR SISWA SEKOLAH DASAR - Sekar Dwi Ardianti, S.Pd., M.Pd; Savitri Wanabuliandari; Moh. Kanzunnudin (Universitas Muria Kudus, 2019)
The purpose of this study was to determine the improvement of the character of homeland love for elementary school students through the application of ethno-edutainment-based learning. This research is a pre-experimental study with one group pretest post test design research design. The sample used in this study was a fifth grade student of Muhammadiyah Kudus Elementary School with a purposive sampling technique. Data on students' love of homeland characters was obtained using student observation sheets and analyzed using normalized gain tests. The results showed that students' homeland love character scores after learning were higher, reaching 12.54 compared to before learning with a score of 6.36. The results of the normalized gain analysis show that the level of increase in the love character of the homeland students in the low category was 4.55%, the medium category was 40.91%, and the high category was 54.54%. Classically, the value of normalized gain <g> is 72% or 0.72, which means that the interpretation of the increase in the character of love for the country is high